Efektivitas E-Modul dalam Meningkatkan Literasi Keuangan pada Usaha, Mikro, Kecil dan Menengah (UMKM) Perempuan Pesisir - Hafidah, Andi; Sartika S., Sartika S.; Gafur, Gafur; Haris, Risma; Hadi, Abri; Ardianto, Wildan (Jurnal Maksipreneur, 2025)
Financial literacy remains a major challenge for coastal women-owned MSMEs in South Sulawesi, particularly those engaged in fisheries, food processing, and local handicrafts. A limited understanding of formal financial products and the absence of systematic record-keeping have hindered their business competitiveness. This study aims to evaluate the effectiveness of an e-module as a digital learning medium in improving the financial literacy of coastal women entrepreneurs. The research employed a quasi-experimental design with a pre-test and post-test control group. A total of 60 respondents were selected purposively from four regions: Makassar City, Palopo City, Takalar Regency, and Pinrang Regency. Data were collected using a structured questionnaire with high reliability. The findings revealed a significant improvement in financial literacy among the experimental group, with an average N-Gain Score of 62.12% (moderately effective), compared to the control group, which achieved 48.78% (less effective).